Analysis of the Ecotourism Potential of the Mount Mekongga Protected Forest, North Kolaka Regency, Southeast Sulawesi Province - Yusran; Tutut Sunarminto; Rachmad Hermawan (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
Abstract: The protected forest of Mount Mekongga is the upstream of three major rivers that empties into Kolaka Regency and North Kolaka Regency, which play an important role in the lives of the surrounding community. The conditions that have occurred so far have been threatened in the form of encroachment, illegal logging, and animal hunting. This is a threat that will lead to forest area degradation in the future. The purpose of this study was to identify and assess the potential of tourism resources in the protected forest of Mount Mekongga. Data collection was carried out in March-July 2022, data collection methods tended towards field observations and visual observations, in-depth interviews were conducted with the community and managers, and literature studies. Tourism potential analysis refers to the assessment criteria of Avenzora (2008) which include 7 associative criteria, namely uniqueness, rarity, beauty, seasonality, accessibility, sensitivity, social function. The tourism potential assessed is the potential for natural tourism, consisting of flora, fauna, natural phenomena. Each variable produces superior potential, namely the fiber orchid, the sulawesi julang, and the tinukari river